Population alterations of l-arginase- and inducible nitric oxide synthase-expressed CD11b⁺/CD14⁻/CD15⁺/CD33⁺ myeloid-derived suppressor cells and CD8⁺ T lymphocytes in patients with advanced-stage non-small cell lung cancer - Liu, Chien-Ying; Wang, Yu-Min; Wang, Chih-Liang; Feng, Po-Hao; Ko, How-Wen; Liu, Yun-Hen; Wu, Yi-Cheng; Chu, Yen; Chung, Fu-Tsai; Kuo, Chih-Hsi; Lee, Kang-Yun; Lin, Shu-Min; et al. (Journal of cancer research and clinical oncology, 2010)
Background Immune aberrations have been demonstrated in tumorogenesis, and myeloid-derived suppressor cells (MDSC) have shown to play a pivotal role in mediating immune suppression in animal models of human tumors. In the present study, we explored the clinical relevance of CD11b⁺/CD14⁻/CD15⁺/CD33⁺ MDSCs and the association of MDSCs with CD8⁺ cytotoxic T lymphocytes in patients with non-small-cell lung cancer (NSCLC). Patients and methods The population of CD11b⁺/CD14⁻ cells in peripheral blood mononuclear cells (PBMNC) was determined in 173 patients with NSCLC and 42 control subjects. The expression of CD15, CD33, IL-4R, INF-γR, iNOS and l-arginase were analyzed. Cocultures with CD8⁺ T lymphocytes and Jurkat cells were developed to determine the impact of MDSCs on the expression of CD3ζ of CD8⁺ T lymphocytes. Results Patients with treatment-naïve, advanced-stage NSCLC (n = 87) had an increased subpopulation of CD11b⁺/CD14⁻/CD15⁺/CD33⁺ cells in the PBMNCs with characteristics of MDSCs (P < 0.0001). The CD11b⁺/CD14⁻ cells in PBMNC also express IL-4R and INF-γR and can suppress CD3ζ expression in CD8⁺ T lymphocytes. The subpopulation of CD11b⁺/CD14⁻ cells in PBMNC was decreased in the advanced-stage NSCLC patients who had responsiveness to chemotherapy (n = 41, P < 0.0001) and in the early-stage NSCLC patients after removal of tumor (n = 8, P = 0.0391). Notably, a negative association existed between the population of CD11b⁺/CD14⁻ cells in PBMNC and the frequency of CD8⁺ T lymphocytes (n = 48, r = −0.3141, P = 0.0297). Conclusions Our study provided evidence of an increased pool of CD11b⁺/CD14⁻/CD15⁺/CD33⁺ MDSCs in the peripheral blood of NSCLC patients. For the suppressive effect of the cells on CD8⁺ T lymphocytes, these findings suggest the important role of the CD11b⁺/CD14⁻/CD15⁺/CD33⁺ MDSCs in mediating immunosuppression in NSCLC.